Analysis of Household Waste Volume in North Banjarbaru District, Banjarbaru City - Almira Ulimaz; Nana Citrawati Lestari (Green Visioneers, 2019)
Increasing the number of residents in the city of Banjarbaru certainly increases the amount of waste generated. This study aims to analyze the generation of household waste volume in the City of Banjarbaru. Specifically, this research is focused on the people who live and live in the District of North Banjarbaru . Quantitative research was conducted to determine the generation of household waste volume while qualitative research was conducted to analyze how later good waste management could be carried out in the region based on obtained research data. Research samples for data about garbage generation is 50 households. Data is processed descriptively through data tabulation . The results of research on the generation of household waste volume is 0.4 868 kg / capita per day . Based on the data generated from the solid waste volume based on the existing population, the required fleet projections from the Banjarbaru City Sanitation Department are at least seven transport trucks, while currently only two garbage trucks are available.